COMPARISION OF DIFFERENT TECHNIQUES FOR MITIGATION OF UNDER VOLTAGE PROBLEM OF BANGLADESH POWER SYSTEM AND THEIR EFFECT ON STABILITY - Sarker Utsha, Manobendro; Nabil, Shadman Shakib; Rahman, Md. Mahmudur (DEPARTMENT OF ELECTRICAL, ELECTRONIC AND COMMUNICATION ENGINEERING, 2017)
Power quality has become a major concern because of increasing number of loads being connected to the power system. Abnormal conditions in a power system create fluctuations to electrical quantities such as voltage, frequency and current. An important factor in the normal and healthy operation of the power system is to maintain security in power generation, transmission and distribution. System security can be assessed by solving under-voltage problem. In this thesis power flow analysis of Bangladesh Power System is performed by PSAF (Power System Analysis Framework) and three different solution method of under-voltage problem is shown along with cost calculation for each of the methods. Afterward, transient stability analysis is done for each of the methods considering four different abnormal events taking one at a time. A comparative conclusion is shown on the basis of cost effectiveness and stability for the adopted solution methods.
First and foremost, praises and thank to the God, the Almighty, for His showers of blessings throughout our B.Sc. research work to complete the research successfully in due time. We would express our deep and sincere gratitude to our research supervisor, Mr. Hamidur Rahman, Associate Professor, Department of Electrical and Electronic Engineering, BUET, Dhaka, for his continuous support of our research, for his patience, motivation, enthusiasm, and immense knowledge throughout the thesis. We feel grateful to him for giving us sufficient freedom and having faith in our capabilities, which made the research work very much enjoyable for us. His guidance helped us in all the time of research and writing of the thesis. We could not have imagined having a better advisor and mentor for our thesis study. We also acknowledge that without his supervision this work would not have been possible. Our whole hearted thanks to the department of Electrical, Electronic and Communication Engineering at Military Institute of Science and Technology for all the resources that helped us in successfully completing our degree requirements. The authors also express their sincere gratitude to all those people who have collaborated in this work. Last but not the least, and most importantly the authors would like to thank their parents, for driving force and standing by us through thick and thin. It is only the unparalleled love, support and vision of our parents that made this work a reality.